CCAFS and partners influenced more than USD 3.5 billion CSA investments globally over the last 10 years - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS and partners' three investment outcome pathways are associated with more than USD 3.5 billion CSA investments globally